2013
DOI: 10.1109/tmi.2012.2219626
|View full text |Cite
|
Sign up to set email alerts
|

A Virtual Coiling Technique for Image-Based Aneurysm Models by Dynamic Path Planning

Abstract: Computational algorithms modeling the insertion of endovascular devices, such as coil or stents, have gained an increasing interest in recent years. This scientific enthusiasm is due to the potential impact that these techniques have to support clinicians by understanding the intravascular hemodynamics and predicting treatment outcomes. In this work, a virtual coiling technique for treating image-based aneurysm models is proposed. A dynamic path planning was used to mimic the structure and distribution of coil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 34 publications
2
29
0
Order By: Relevance
“…carotid arteries, basilar trunk, and the circle of Willis) are the focus of multiple investigations and references therein). In this context, blood flow computational models are relevant to various clinical applications, such as check-up and follow-up of aneurysms (Cebral et al (2005); Shojima et al (2014); Retarekar et al (2015)) and control after stenting (Wang et al (2011)) or coiling (Morales et al (2013)). In contrast, the behavior of the venous cerebral system is rarely explored.…”
Section: Introductionmentioning
confidence: 99%
“…carotid arteries, basilar trunk, and the circle of Willis) are the focus of multiple investigations and references therein). In this context, blood flow computational models are relevant to various clinical applications, such as check-up and follow-up of aneurysms (Cebral et al (2005); Shojima et al (2014); Retarekar et al (2015)) and control after stenting (Wang et al (2011)) or coiling (Morales et al (2013)). In contrast, the behavior of the venous cerebral system is rarely explored.…”
Section: Introductionmentioning
confidence: 99%
“…Combined with virtual interventions (e.g. Larrabide et al, 2012;Morales et al, 2013), this approach enables execution of in silico clinical trials (Viceconti et al, 2016) or supporting of regulatory processes (Center for Devices and Radiological Health, 2014) especially in scenarios that could be impractical, costly or unethical (e.g. Larrabide et al, 2013;Morales et al, 2011) to carry out in animals or humans as a first line of choice.…”
Section: The Trend: From Data To Wisdom and Backmentioning
confidence: 99%
“…The work by Morales et al [27] present a method based on dynamic path planning to model the distribution of embolization coils in cerebral aneurysms. The virtual coiling technique reproduces the macroscopic behavior of inserted coils and properly captures the densities, shapes and coil distributions inside aneurysmal cavities.…”
Section: Special Issue Contentmentioning
confidence: 99%
“…Modeling for Interventional Planning: The work by Morales et al [27] showed how the combination of device modeling and virtual deployment, in addition to patient-specific image-based anatomical modeling, can help to carry out patient-specific treatment plans and assess alternative therapeutic strategies. Although a number of such approaches have already been introduced in the literature [73]- [79], further research efforts will be invested in modeling devices and interventions as well as the interplay between the devices and relevant biological processes [80]- [84].…”
Section: ) Image-based and Patient-specific Virtual Treatmentmentioning
confidence: 99%